Economic scarcity and consumers' credit choice - Marieke Bos; Chloé Le Coq; Peter van Santen (Sveriges Riksbank, 2016)
This paper documents that increased scarcity right before a payday causally impacts credit choices. Exploiting a transfer system that randomly assigns the number of days between paydays to Swedish social welfare recipients, we find that low educated borrowers behave as if they are more present-biased when making credit choices during days when their budget constraints are exogenously tighter. As a result their default risk and debt servicing cost increase significantly. Access to mainstream credit or liquidity buffers cannot explain our results. Our findings highlight that increased levels of economic scarcity risk to reinforce the conditions of poverty.
Keywords: G02; G23; D14; D81; 330; household finance; present bias; scarcity; credit choice